Pulsation-induced Spectroscopic Variability of IRAS Z02229+6208 - Laimons Začs; Kārlis Puķı̄tis (The Astrophysical Journal, 2023)
Monitoring of high-resolution spectra in the optical and near-infrared wavelength region was carried out for the early post-AGB stage star IRAS Z02229+6208 with the CARMENES instrument to reveal spectroscopic variability over the pulsation cycle of 154 days. Significant changes are seen in both the intensity and position of carbon-bearing molecular lines. Strong and broad CN red system lines, blueshifted up to 9.4 km s ^−1 relative to the stellar photosphere, are seen near the light minimum. Near the light maxima, the molecular features are weak and most of them are in emission, e.g., broad emissions in the CN red system (0,0) lines are seen. A site of formation of molecular absorptions and emissions appears to be an extended atmosphere of a cool post-AGB star affected by stellar pulsation. In addition, we observed narrow absorption lines of the C _2 Phillips (2, 0), (3, 0) system and the CN red system (2,0), most likely related to the circumstellar envelope produced during the evolution on the asymptotic giant branch (AGB). An expansion velocity of the circumstellar shell was found to be V _exp = −11.1 km s ^−1 relative to the stellar mass center, in agreement with that estimated before from CO lines. The observed spectroscopic variability seems to be typical for pulsating early post-AGB stage stars.